Gepants: targeting the CGRP pathway for migraine relief - Jakubowska, Bernadetta; Sowa-Kućma, Magdalena (Frontiers in Pharmacology, 2025)
BackgroundCalcitonin gene–related peptide (CGRP) receptor antagonist (collectively known as gepant) have emerged as effective therapies for both acute migraine treatment and preventive management. Several new agents (atogepant, ubrogepant, rimegepant, and zavegepant) expand therapeutic options beyond traditional triptans and monoclonal antibodies.ObjectiveTo summarize and critically evaluate the pharmacology, clinical efficacy, safety, and positioning of currently approved gepants for migraine treatment and prevention.MethodsA structured literature search was performed in PubMed/MEDLINE, Embase, Web of Science, Scopus, Cochrane Library, and ClinicalTrials.gov for studies published from 1998 to September 2025. Search terms included “gepant,” “CGRP receptor antagonist,” “atogepant,” “ubrogepant,” “rimegepant,” “zavegepant,” “pharmacokinetics,” “efficacy,” and “safety,” combined with Boolean operators. Peer-reviewed clinical studies providing data on pharmacology, efficacy, or safety were included; case reports, conference abstracts, and non-English articles were excluded.ResultsFour gepants are currently approved for clinical use. Atogepant is indicated solely for prevention, while ubrogepant and zavegepant are approved for acute treatment; rimegepant is approved for both indications. All agents exhibit favorable pharmacokinetic profiles, with oral or intranasal formulations enabling rapid onset and convenient dosing. Across randomized controlled trials, gepants demonstrated significant reductions in monthly migraine days for prevention and high rates of 2-h pain freedom in acute treatment compared with placebo. Safety profiles were generally benign, with mild adverse events such as nausea and fatigue and no evidence of vasoconstriction or hepatotoxicity in contemporary studies.ConclusionGepants represent a valuable advancement in migraine therapy, offering effective acute and preventive options with favorable tolerability, particularly for patients who cannot use triptans or who have cardiovascular risk factors. Ongoing studies will clarify long-term safety, real-world effectiveness, and potential roles in combination or sequential therapy.